Staining of wool using the reaction products of ABTS oxidation by Laccase : synergetic effects of ultrasound and cyclic voltammetry - Munteanu, Florentina-Daniela (2007)
The effects of ultrasound on 2,2′-Azinobis(3-ethylbenzothiazoline-6-sulfonate) enzymatic oxidation by laccase (Trametes villosa) has been studied by means of cyclic voltammetry. The reaction was allowed to proceed in the presence of a piece of wool and the coloration depth of the wool fabric was measured by means of K/S. It was observed that cyclic voltammetry is influenced the dyeing process and higher K/S values were obtained when the cyclic voltammetry was combined with the ultrasonic irradiation. Moreover, the K/S value is the sum of the values obtained when the wool staining is done in just the presence of cyclic voltammetry or in just the presence of ultrasound. The results obtained on the indigo carmine decolourization gives information on the importance of controlling the amount of ABTS+ formed during the ultrasonication process.